Minerals and Metals to Meet the Needs of a Low-Carbon Economy - Hund, Kirsten Lori; La Porta, Daniele; Drexhage, John (World Bank, Washington, DC, 2017)
Meeting the requirements of the Paris Agreement to keep the global average temperature from rising more than 2ºC above pre-industrial levels will mean vastly expanded use of low-carbon sources of electricity, such as wind and solar power, as well as advanced technologies for long-term energy storage. These demands will increase demand for many minerals, including a range of base and rare earth metals. By planning ahead, resource rich developing countries can prepare themselves to meet the challenges and opportunities afforded by increased demand for minerals.